Responsive Surfaces: Magnetically Responsive Elastomer–Silicon Hybrid Surfaces for Fluid and Light Manipulation (Small 2/2018). Issue 2 (11th January 2018) - Yang, Zining; Park, Jun Kyu; Kim, Seok
Abstract : In article1702839, Seok Kim and co‐workers construct a magnetically responsive surface consisting of an array of silicon scales assembled on ferromagnetic elastomer micropillars. Multiple functions, such as droplet manipulation, structural coloration, and tunable optical transmission, are realized by incorporating a wide range of nanostructured silicon scales in a controlled configuration.